La disfuncionalidad familiar y el rendimiento académico en estudiantes de 7mo. Grado de la escuela “Rosa Josefina Burneo de Burneo” Loja, 2023-2024 - Tocto Pineda, Willan Alexander (2024)
This research work addresses dysfunctional family dynamics and their impact on the academic performance of seventh-grade students at the "Rosa Josefina Burneo de Burneo" Basic Education School in Loja, during the 2023-2024 period. Family dysfunction is understood as a set of problematic interactions within the family nucleus that negatively affects its members, perpetuating dysfunctional patterns across generations. The general objective is to analyze how family dysfunction affects students' academic performance. The methodology used was qualitative, descriptive, and non-experimental. The techniques used included interviews and direct observation, with instruments such as the interview guide and observation sheet, validated by three experts. For the analysis, data triangulation was applied, and purposive non- probabilistic sampling was used, focusing on teachers and students with low academic performance. The results show that dysfunctional family dynamics, characterized by conflicts, poor communication, lack of affection and emotional support, as well as manifestations of violence, create a stressful environment that affects students' emotional stability and, consequently, their academic performance. Personal, family, and socioeconomic factors that limit academic performance were also identified, as they hinder the development of capabilities such as motivation, and combined with economic instability, school performance is affected. In conclusion, family dysfunction affects academic performance, as it acts as a barrier that hinders both the integral development and school performance of students.